2020
DOI: 10.1096/fba.2020-00078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transgenic silk materials that incorporate FGF‐7 protein microcrystals on the proliferation and differentiation of human keratinocytes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…To obtain silkworm cocoons containing FGF-7 in the sericin layer, we generated transgenic silkworm line S1sp-F7 carrying FGF-7 cDNA-fused with the polyhedra-encapsulation signal helix-1 sequence (H1/FGF-7) and regulated by the sericin-1 promoter ( Figure 1 A). The fusion with the H1 peptide facilitated the encapsulation of foreign proteins using microcrystals of cypovirus polyhedrin (also known as polyhedra) and showed no adverse effects on the biological activities of the fused proteins, including FGF-7 [ 11 , 28 ]. The stabilization effect of cypovirus polyhedra on encapsulated proteins against the hostile environment [ 11 , 12 , 28 ] drove us to investigate the stability of H1/FGF-7 as a combined effect of encapsulation by polyhedra and incorporation into sericin cocoons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain silkworm cocoons containing FGF-7 in the sericin layer, we generated transgenic silkworm line S1sp-F7 carrying FGF-7 cDNA-fused with the polyhedra-encapsulation signal helix-1 sequence (H1/FGF-7) and regulated by the sericin-1 promoter ( Figure 1 A). The fusion with the H1 peptide facilitated the encapsulation of foreign proteins using microcrystals of cypovirus polyhedrin (also known as polyhedra) and showed no adverse effects on the biological activities of the fused proteins, including FGF-7 [ 11 , 28 ]. The stabilization effect of cypovirus polyhedra on encapsulated proteins against the hostile environment [ 11 , 12 , 28 ] drove us to investigate the stability of H1/FGF-7 as a combined effect of encapsulation by polyhedra and incorporation into sericin cocoons.…”
Section: Resultsmentioning
confidence: 99%
“…The fusion with the H1 peptide facilitated the encapsulation of foreign proteins using microcrystals of cypovirus polyhedrin (also known as polyhedra) and showed no adverse effects on the biological activities of the fused proteins, including FGF-7 [ 11 , 28 ]. The stabilization effect of cypovirus polyhedra on encapsulated proteins against the hostile environment [ 11 , 12 , 28 ] drove us to investigate the stability of H1/FGF-7 as a combined effect of encapsulation by polyhedra and incorporation into sericin cocoons. Therefore, transgenic silkworm line S1sp-F7/poly producing cocoons with sericin layers incorporated with co-expressed H1/FGF-7 and polyhedrin was generated as described in the Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroin-based materials are useful for biomedical applications, such as in fine sutures [6], electrospun nanofiber film-based dressings [7], hydrogels for drug delivery and tissue engineering [8,9], biodegradable carriers for cell growth factors [10,11], and sponge scaffolds for cell growth [12][13][14]. Fibroin-based biomaterials, which are biocompatible, biodegradable, and have low immunostimulatory properties, have been used for revascularization [15], bone tissue regeneration [16], and cutaneous wound healing [17,18].…”
Section: Of 15mentioning
confidence: 99%
“…Fibroin-based biomaterials, which are biocompatible, biodegradable, and have low immunostimulatory properties, have been used for revascularization [15], bone tissue regeneration [16], and cutaneous wound healing [17,18]. Our previous study showed that fibroin powders incorporated with protein microcrystalencapsulated cytokines processed from transgenic silk glands effectively controlled NIH-3T3 proliferation [10] and facilitated the formation of a three-dimensional (3D) epidermis model [11]. These examples highlight the potential of fibroin-based biomaterials that can be generated through the bioengineering of silkworms for biomedical applications, particularly for tissue engineering.…”
Section: Of 15mentioning
confidence: 99%